Estrategia didáctica para la enseñanza y aprendizaje en el laboratorio de circuitos eléctricos de la universidad de la costa cuc - Rita Dederlé-Caballero; Ebaldo Pérez-Villareal; Sandra Lora-Castro; Carlos Peña-Arrieta; Fernando Charris-Chiquillo (Universidad del Magdalena, 2015)
This work is the outcome of a research developed in collaboration with the Academic Group "Estudios en Educación" based on interviews conducted to students and members of the same Academic Group. The purpose for these interviews was resuming, reconstructing and reflecting on their experiences in the implication of the strategy "Formative Research" and the impact that this exercise has had in the professional training of students as possible future researchers, as well as in the improvements in the professional training of researchers regarding the student's knowledge and their contributions in an exercise of "Everyone learn from everyone". This is considered as emerging research experiences show that different groups are taking towards these experiences and disseminate them as references for reproduction, adaptation or exclusion according to the needs and circumstances of those involved in the investigation.